PERAN KONSELING DALAM MENGATASI KRISIS IDENTITAS PADA MAHASISWA AKIBAT GLOBALISASI BUDAYA - Zharima Berlian Ningrum; Crisfatika Yulianti; Annisa Putri Rahmasari; Andini Putri Kusuma; Prasetya Koswara; Ela Nur Fadilah; Ari Khusumadewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of cultural globalization on the formation of student identity, which arises in the conflict between local values, which conflict between collectivism and the global value system of individualism. Students are considered to be in the emerging adult stage of their life journey. Although identity crises, such as role confusion, anxiety, and culture shock, are common, students are particularly vulnerable to them. This article attempts to describe the influence of cultural globalization on student identity, the nature of student identity crises, and the impact of counseling on these issues. This qualitative study uses desk research methods in the form of secondary literature to establish a baseline for the identity crisis phenomenon. The findings indicate that student counseling, particularly within a multicultural framework, provides a valuable opportunity to establish a counseling environment that facilitates self-exploration. Self-exploration and self-reflection techniques in counseling help students choose and limit the adaptation and integration of global cultures into their local culture. Students find positive reinforcement techniques useful in managing and overcoming cultural differences. This encourages students to adopt a positive view of their new environment, allowing them to view it as a non-threatening learning environment. These counseling practices have positive impacts, including increased self-esteem, improved coping skills, and better integration and synthesis of local and global identities.